2003
DOI: 10.1079/pns2003286
|View full text |Cite
|
Sign up to set email alerts
|

Cross talk between physical activity and appetite control: does physical activity stimulate appetite?

Abstract: Abbreviations: EB, energy balance; EE, energy expenditure; EI, energy intake; Hex, high exercise level; Mex, medium exercise level; Nex, no exercise. Physical activity has the potential to modulate appetite control by improving the sensitivity of the physiological satiety signalling system, by adjusting macronutrient preferences or food choices and by altering the hedonic response to food. There is evidence for all these actions. Concerning the impact of physical activity on energy balance, there exists a beli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
190
5
12

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 248 publications
(218 citation statements)
references
References 43 publications
11
190
5
12
Order By: Relevance
“…It is known that there is an uncoupling between energy expenditure and energy intake (53,54), where the low level of energy expenditure does not lead to a corresponding down regulation in energy intake. The classic study by Mayer, Roy and Mitra (55) demonstrated that appetite is poorly regulated at low activity levels.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that there is an uncoupling between energy expenditure and energy intake (53,54), where the low level of energy expenditure does not lead to a corresponding down regulation in energy intake. The classic study by Mayer, Roy and Mitra (55) demonstrated that appetite is poorly regulated at low activity levels.…”
Section: Discussionmentioning
confidence: 99%
“…We were interested to investigate whether exercise could affect AMPK activity in the hypothalamus, thereby providing a potential mechanism for the coordination of energy expenditure and energy intake during or following exercise. For instance, exercise leads to changes in appetite such that appetite is suppressed during strenuous exercise and a short while after exercise [18; 19] whereas increases in appetite after a single bout of exercise are not always found [19]). These changes in appetite could therefore be expected to stem from changes in hypothalamic AMPK activity.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise leads to changes in appetite such that appetite is suppressed during strenuous exercise [18; 19] and a short while after exercise whereas increases in appetite after a single bout of exercise are inconsistent (For review see [19]). The mechanism behind this exercise-induced change in appetite is not known [19] but could involve changes in hypothalamic AMPK activity which may serve the function of coordinating energy expenditure during exercise with energy intake during or after exercise.…”
Section: Introductionmentioning
confidence: 99%
“…50 The adipocytokines, under normal weight conditions, guarantee homeostasis of glucose and lipid metabolism, but their dysregulated production in the obese state is associated with 52 and that compensatory responses in intake to altered levels of exercise may not begin to act until the excess energy stores become depleted and the energy homeostasis is at risk. 3 …”
Section: Article In Pressmentioning
confidence: 99%